Penerapan Pembelajaran Probing-Prompting untuk Meningkatkan Hasil Belajar Materi Bangun Ruang pada Siswa Kelas VI MIN Kota Blitar tahun pelajaran 2021/2022 - Hidayana, Anis (Center of Education Journal (CEJou), 2022)
The selection of learning methods greatly determines the quality of learning in the teaching and learning process in the classroom. Based on the results of interviews conducted by researchers with mathematics teachers in parallel grade VI MIN Blitar City, information was obtained that: 1) students whose scores were less than 75 were still 10 students more than 28 students, 2) there were still many students who were not ready to participate in activities learning, 3) the involvement of students in the learning process is still less active, 4) the madrasa has not yet carried out learning with the probing-prompting learning method in mathematics learning, especially spatial building materials. To overcome these problems, the researchers used the probing-prompting learning method as an effort to improve the learning outcomes of building materials. This research is a qualitative research in the form of classroom action which is designed in a cycle. The subjects in this study were grade VI students of MIN Blitar City in the 2021/2022 academic year. Data collection in this study was carried out by tests, observations, and questionnaires. The instruments used in this study were lesson plans, test questions, observation sheets, and questionnaire sheets. The data analysis used is non-statistical data analysis, namely descriptive analysis. This analysis model by comparing the average percentage. The results of the study indicate that the application of probing-prompting learning in learning can improve learning outcomes of quadrilateral material in grade VI students of MIN Blitar City in the 2021/2022 academic year. This can be seen from the results of the study. The results of observations showed that the teacher's activity in the first cycle the average score was 66.65% while in the second cycle the average score was 87.45% and the student activity in the first cycle the average score was 65.63%, while in the second cycle the average score was 65.63%. II the average score is 86.46%. The test results in the first cycle showed that 16 students had completed their studies with classical mastery of 57%, while in the second cycle there was an increase of 39%, namely 27 students who had completed their studies with 96% classical completeness. Based on the results of student questionnaires, the probing-prompting learning method got a response of 64.64% in the first cycle and got a good response from the students in the second cycle, which was 84.46% interested in being applied to the next lesson.